2015
DOI: 10.17306/j.afw.2015.1.0
|View full text |Cite
|
Sign up to set email alerts
|

An attempt at valuation of wood from dead trees in Polish forests

Abstract: Abstract. This study suggests a method of valuation for wood coming from dead trees which was applied for pricing of such wood found in Polish forests. This study shows that in Polish forest there are approx. 52 million m 3 biocenotic wood coming from dead or dying trees with an estimated value of 1.5 billion PLN/10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Recent years have seen an increased demand for biomass used for the production of a variety of liquid and gaseous fuels, improved solid fuels, such as pellets and briquettes, and for direct combustion (Rosendahl 2013;Ociepa-Kubicka 2015;Uliasz-Bocheńczyk and Mokrzycki 2015). This is directly linked to climate change and the effects of acid rain, which motivate scientists to seek and develop new methods of heat and electricity production (Ghaly and Mansaray 1999;Jabłoński and Stempski 2015;Ociepa-Kubicka 2015). According to Cardoso et al (2011), approximately 14% of the total demand for energy worldwide is covered by biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen an increased demand for biomass used for the production of a variety of liquid and gaseous fuels, improved solid fuels, such as pellets and briquettes, and for direct combustion (Rosendahl 2013;Ociepa-Kubicka 2015;Uliasz-Bocheńczyk and Mokrzycki 2015). This is directly linked to climate change and the effects of acid rain, which motivate scientists to seek and develop new methods of heat and electricity production (Ghaly and Mansaray 1999;Jabłoński and Stempski 2015;Ociepa-Kubicka 2015). According to Cardoso et al (2011), approximately 14% of the total demand for energy worldwide is covered by biomass.…”
Section: Introductionmentioning
confidence: 99%
“…It affects soil development, C stores, nutrients and water and reduces erosion at the same time (Kupferschmidt et al 2003;Pichler et al 2011). According to Adamowicz et al (2015), Polish forests have approximately 52 million m 3 of wood that originates from dead trees. The amount of organic matter and soil C stocks are dependent on the vegetation, site conditions and forest management practices (Yin 1999;Debeljak 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some authors indicated the problem with an adequate definition of forest, which also affects the value of the forest cover index. In Poland, forests are protected within the framework of three groups of functions, that is, productive, ecological and social (Zając 2001;Płotkowski 2004;Zając and Gołos 2008;Adamowicz and Kaciunka 2014;Kaliszewski and Młynarski 2014;Adamowicz et. al 2015;Kaliszewski 2016;Szramka et al 2016).…”
Section: Discussionmentioning
confidence: 99%